(untitled) (Nativa, 2018)
Este estudo analisou quais são as estruturas públicas e necessidades voltadas ao desenvolvimento rural sustentável nos municípios lindeiros ao lago da Usina Hidroelétrica de Itaipu, seus problemas ambientais e suas necessidades. Trata-se de um trabalho de cunho descritivo de abordagem qualitativa. Os dados foram coletados por meio de um questionário com 66 questões aplicados aos doze gestores das secretarias de agricultura e meio ambiente dos doze municípios lindeiros ao lago da usina. Os dados foram apresentados em porcentagem e analisados de maneira descritiva. Os resultados da pesquisa revelam que os municípios lindeiros pesquisados evidenciam como principais problemas ambientais a contaminação da água, do solo e o descarte irregular de lixo rural, com relação as suas necessidades para o desempenho das funções 92% dos gestores das secretarias revelam que seriam necessários aportes de recursos financeiros, para sanar estes problemas. Palavras-chave: municípios lindeiros, sustentabilidade, políticas públicas, problemas ambientais. ANALYSIS OF THE PUBLIC STRUCTURES RETURNED TO SUSTAINABLE RURAL DEVELOPMENT IN THE MUNICIPALITIES LINDEIROS TO THE LAKE OF THE ITAIPU HYDROELECTRIC POWER PLANT ABSTRACT: This study analyzed public structures aimed at sustainable rural development in the municipalities bordering the lake of the Itaipu hydroelectric power plant, their environmental problems and their needs. This is a descriptive work with a qualitative approach. The primary source data were collected through a structured interview applied to the managers of the agriculture and environmental departments of the twelve municipalities bordering the lake of the Itaipu plant. The data were treated in percentage and analyzed in a descriptive way. The results of the research show that the surveyed municipalities show that the main environmental problems are contamination of water, soil and the irregular disposal of rural waste, in relation to their needs for the performance of the functions. 92% of the managers of the secretariats show that they would be necessary Resources to address these problems. Keywords: sustainable rural development, lindeiros municipalities, public policy, environmental problems.